Moeling Mercury Uptake In The Everglades Algae. - Shamlan, Munir Bin; Koh, Hock Lye; Lee, Hooi Ling (2005)
The presence of mercury in the aquatic food chain has always been a concern due to its accumulative effects in the chain. Over the last 100 years the average global atmospheric mercury concentration has increased by five fold from 0.3 ng m-3 to 1.5 ng m-3. The two main sources of atmospheric mercury emissions are natural sources such as volcanoes and solis, and anthropogenic sources that include combustion and waste incineration.......